The Influence of Capital Market and Investment Literacy on Students’ Interest in ESG-Based Investment in South Sulawesi, Indonesia - Muhammad Irfai Sohilauw (Khazanah Sosial, 2025)
This study aims to examine how capital market knowledge and investment literacy influence university students’ interest in ESG (Environmental, Social, and Governance)-based investments, with a particular focus on the mediating role of perceived ESG benefits. The research addresses the growing urgency of sustainable finance and the gap in ESG awareness among student investors in Indonesia. Using a descriptive quantitative approach, the study collected primary data through a structured online questionnaire distributed to 98 active members of the South Sulawesi Capital Market Study Group Forum (Forum Komunikasi Kelompok Studi Pasar Modal Sulawesi Selatan-FKSS). The data were analysed using Structural Equation Modeling (SEM) with SmartPLS to test both direct and mediating effects between constructs. The results show that both capital market knowledge and investment literacy have a significant positive effect on students' perceptions of ESG benefits and their interest in ESG-based investments. The perceived benefits of ESG investments act as a strong mediating variable, indicating that financial knowledge enhances students’ willingness to engage in sustainable investing when they appreciate its long-term value. These findings suggest the need for enhanced ESG-related financial education in university curricula and greater standardisation in ESG reporting to build trust and understanding among young investors. Policymakers and regulators should collaborate with educational institutions to promote sustainable investment literacy among students. This study offers a novel contribution by focusing on student-level ESG investment behaviour in Indonesia, a demographic underexplored in ESG literature. It highlights the cognitive mechanisms through which financial literacy translates into sustainable investment interest, offering fresh insights into the promotion of responsible investing in emerging markets.